Natural convection semi-cylindrical cavity with heat flux boundary conditions into the system - 190574 Saiddi Ali Firdaus Mohamed Ishak; Amer Nordin Darus; Fakulti Kejuruteraan Mekanikal (2006)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006